Visual input regulates melanophore differentiation - Atkinson-Leadbeater, Karen; Bertolesi, Gabriel E.; McFarlane, Sarah (Frontiers in Cell and Developmental Biology, 2024)
Developmental processes continue in organisms in which sensory systems have reached functional maturity, however, little research has focused on the influence of sensory input on cell and tissue development. Here we explored the influence of visual system activity on the development of skin melanophores in Xenopus laevis, where altering visual input via rearing larvae on a black background or eye enucleation, leads to an increase in melanophores in the perioptic region of the head. We found that at the time when the visual system becomes functional, Xenopus larvae possess a population of undifferentiated melanophores that can respond rapidly to changes in the external light environment by undergoing differentiation. Enucleation, or maintaining larvae on a black background, increases the expression of melanization genes tyr, tyrp1, and pmel. Conversely, maintaining larvae in full light suppresses melanophore differentiation. Interestingly, the transition to differentiated melanophores relies on an extrapineal melatonin signal. Thus, we propose a novel mechanism of environmental influence where external sensory signals influence cell differentiation in a manner that would favor survival.